Adhesion of MRC‐5 and A549 cells on poly(dimethylsiloxane) surface modified by proteins. Issue 3 (30th September 2015) - Zuchowska, Agnieszka; Kwiatkowski, Piotr; Jastrzebska, Elzbieta; Chudy, Michal; Dybko, Artur; Brzozka, Zbigniew
Abstract : PDMS is a very popular material used for fabrication of Lab‐on‐a‐Chip systems for biological applications. Although PDMS has numerous advantages, it is a highly hydrophobic material, which inhibits adhesion and proliferation of the cells. PDMS surface modifications are used to enrich growth of the cells. However, due to the fact that each cell type has specific adhesion, it is necessary to optimize the parameters of these modifications. In this paper, we present an investigation of normal (MRC‐5) and carcinoma (A549) human lung cell adhesion and proliferation on modified PDMS surfaces. We have chosen these cell types because often they are used as models for basic cancer research. To the best of our knowledge, this is the first presentation of this type of investigation. The combination of a gas‐phase processing (oxygen plasma or ultraviolet irradiation) and wet chemical methods based on proteins' adsorption was used in our experiments. Different proteins such as poly‐l ‐lysine, fibronectin, laminin, gelatin, and collagen were incubated with the activated PDMS samples. To compare with other works, here, we also examined how ratio of prepolymer to curing agent (5:1, 10:1, and 20:1) influences PDMS hydrophilicity during further modifications. The highest adhesion of the tested cells was observed for the usage of collagen, regardless of PDMS ratio. However, the MRC‐5 cell line demonstrated better adhesion than A549 cells. This is probably due to the difference in their morphology and type (normal/cancer).